Characterisation of the adenovirus preterminal protein and its interaction with the POU homeodomain of NFIII (Oct-1). - Botting, C H (1999)
Formation of the preinitiation complex for adenovirus DNA replication involves the incoming preterminal protein-adenovirus DNA polymerase heterodimer being positioned at the origin of replication by protein-DNA and protein-protein interactions. Preterminal protein directly binds to the cellular transcription factor nuclear factor III (Oct-1), via the POU homeodomain. Co-precipitation of POU with individual domains of preterminal protein expressed by in vitro translation indicated that POU contacts multiple sites on preterminal protein. Partial proteolysis of preterminal protein in the presence or absence of POU homeodomain demonstrated that many sites accessible to proteases in free preterminal protein were resistant to cleavage in the presence of POU homeodomain. The accessibility of sites in free preterminal protein to cleavage by trypsin was strongly dependent on the ionic strength, suggesting that preterminal protein may undergo a sodium chloride-induced conformational change. It is therefore likely that the POU homeodomain contacts a number of sites on preterminal protein to induce a conformational change which may influence the initiation of adenovirus DNA replication.